Trace metal determination in total atmospheric deposition in rural and urban areas - Azimi, S.; Ludwig, A.; Thevenot, D.R.; Colin, J.L. (Sci. Total Environ., 2003)
The wet, dry and total atmospheric depositions of some metals (Al, Cd, Cr, Cu, Fe, Na, Pb and Zn) were sampled at two sites and atmospheric fallout fluxes were determined for these locations. This work, led by two different research groups, allowed to reach two main goals: to define a simple analytical procedure to secure accurate shipboard sampling and analysis of atmospheric deposition, and to assess anthropogenic impacts of heavy metals to the environment. The first step about the validation step showed that the prevalent deposition type was dry deposition which represents 40, 60 and 80% for Cd, Cu and Ph, respectively. This prevalence of dry deposition in total atmospheric fallout supported the necessity of funnel wall rinsing which contains 30, 50 and 40% of collected Cd, Cu and Pb, respectively. Moreover, the reproducibility of atmospheric deposition collection was determined. The second step was performed by comparing two sampling sites. A rural sampling site, situated in Morvan’s regional park (250 km south-east of Paris), was chosen for its isolation from any local and regional contamination sources. Fluxes obtained in this area were compared with those obtained at an urban site (Creteil, suburb of Paris) allowing comparison between urban and rural areas and demonstrating the impact of anthropogenic activities on atmospheric deposition of Cr, Cu and Pb. (C) 2002 Elsevier Science B.V. All rights reserved.